Volatile Oil of Amomum villosum Inhibits Nonalcoholic Fatty Liver Disease via the Gut-Liver Axis. (19th July 2018) - Lu, Shanhong; Zhang, Ting; Gu, Wen; Yang, Xingxin; Lu, Jianmei; Zhao, Ronghua; Yu, Jie
Abstract : Background . The dried mature fruit of Amomum villosum has been historically used in China as food and in the auxiliary treatment of digestive system disorders. Numerous studies have shown that gastrointestinal function is closely related to the development of nonalcoholic fatty liver disease via the "gut-liver" axis. Objective . The present study aimed to explore whether the mechanism underlying the regulation of lipid accumulation in nonalcoholic fatty liver disease (NAFLD) may affect related disorders using the active ingredients in A. villosum . Design . Male Sprague-Dawley rats on a high-fat diet (HFD) to induce NAFLD were administered water extract of A. villosum (WEAV), volatile oil of A. villosum (VOAV), or bornyl acetate. After treatment, serum and liver total cholesterol (TC), triglyceride (TG), free fatty acid (FFA), aspartate aminotransferase (AST), alanine aminotransferase (ALT), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were measured. The regulatory role of A. villosum in the microecology of the intestines was assessed using the V4 region of the 16S rDNA sequencing. The expression of the intestinal tight junction proteins occludin and ZO-1 was also measured. The influence of A. villosum on TLR4-mediated chronic low-grade inflammation was evaluated based on the concentrations of key proteins of the TLR4/NF-кB signaling pathway. Results. A. villosum effectively inhibited endogenous lipid synthesis, reduced TG, TC, and FFA accumulation, regulated the expression of LDL-C, and decreased lipid accumulation in liver tissues. VOAV effectively regulated the intestinal microflora, improved chronic low-grade inflammation by promoting ZO-1 and occludin protein expressions, and inhibited the TLR4/NF-кB signaling pathway. Conclusion. The present study provides scientific basis for the potential application of A. villosum in NAFLD prevention and treatment. Additional chemical constituents other than bornyl acetate also contributed to the preventive effects of A. villosum on NAFLD.